2018
DOI: 10.3390/microorganisms6010015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rumen and Manure Microbiomes and Implications for the Inoculation of Anaerobic Digesters

Abstract: Cattle manure is frequently used as an inoculum for the start-up of agricultural biogas plants or as a co-substrate in the anaerobic digestion of lignocellulosic feedstock. Ruminal microbiota are considered to be effective plant fiber degraders, but the microbes contained in manure do not necessarily reflect the rumen microbiome. The aim of this study was to compare the microbial community composition of cow rumen and manure with respect to plant fiber-digesting microbes. Bacterial and methanogenic communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 44 publications
2
40
1
1
Order By: Relevance
“…This results also implied that the rumen fluid had specialized enzymes secreted by the indigenous microorganisms for lignocellulose degradation, the presence of this microbial community have been detected through several modern molecular techniques [29]. Several investigations in the potential microorganism of rumen fluid were carried out, a significant reduction in content was achieved on cellulose in 72 h treatment as much as 23%, and it was found that the dominated microorganism was Firmicutes, and this particular group of bacteria are the potential cellulase producer [30], [31].…”
Section: Figurementioning
confidence: 59%
“…This results also implied that the rumen fluid had specialized enzymes secreted by the indigenous microorganisms for lignocellulose degradation, the presence of this microbial community have been detected through several modern molecular techniques [29]. Several investigations in the potential microorganism of rumen fluid were carried out, a significant reduction in content was achieved on cellulose in 72 h treatment as much as 23%, and it was found that the dominated microorganism was Firmicutes, and this particular group of bacteria are the potential cellulase producer [30], [31].…”
Section: Figurementioning
confidence: 59%
“…The four bacteria families (Bacteroidaceae, Prevotellaceae, Ruminococcaceae, and Clostridiaceae) dominated in the yak fecal microbiome have also been detected as the main producers for CAZymes in the cattle rumen microbiome [26]. However, the Fibrobacteres bacteria, which are important degraders of cellulose and are often highly abundant in the bovine rumen [31,32], were found to be lowly abundant in the yak fecal microbiome (Additional le 3). Besides, Paenibacillaceae within the class Bacilli was the third abundant population among all microbial producers contributing to the PL-encoding genes in the fecal microbiome of yak.…”
Section: Diversity Of Carbohydrate-degrading Enzymes and Microbial Comentioning
confidence: 99%
“…The four bacteria families (Bacteroidaceae, Prevotellaceae, Ruminococcaceae, and Clostridiaceae) dominated in the yak fecal microbiome have also been detected as the main producers for CAZymes in the cattle rumen microbiome [26]. However, the Fibrobacteres bacteria, which are important degraders of cellulose and are often highly abundant in the bovine rumen [31,32], were found to be lowly abundant in the yak fecal microbiome (Additional le 3). Besides, Paenibacillaceae within the class Bacilli was the third abundant population among all microbial producers contributing to the PLencoding genes in the fecal microbiome of yak.…”
Section: Diversity Of Carbohydrate-degrading Enzymes and Microbial Comentioning
confidence: 99%